The rise and fall of Varanopidae† (Amniota, Synapsida) - Laurin, Michel; Didier, Gilles (Frontiers in Earth Science, 2025)
Study of past biological crises is now a timely topic because we may be in the midst of an anthropogenic mass extinction event. A skyline Fossilized Birth-Death (FBD) analysis of a dataset of 21 varanopid taxa, ranging in geological age from the mid-Pennsylvanian to the late Guadalupian, was undertaken to assess the impact of putative mass extinction events on the Varanopidae. Our results suggest that this clade diversified in the Pennsylvanian but dwindled in diversity in the Cisuralian. This is reminiscent of the evolution of biodiversity displayed by ophiacodontids, edaphosaurids and sphenacodontids (abbreviated “the OES grade” from here on) in the same time interval. These patterns are possibly linked to a warming and aridification trend (perhaps local and linked to movements of plates in Pangea) that spanned most of the Early Permian. However, contrary to these last three clades (OES), varanopids survived until near the end of the Capitanian; this differential fate may be linked to differences in habitat use (mainly lowland for the OES grade; often more upland for varanopids). Models that include a mass extinction event that eliminated all varanopids in the late Capitanian, when a mass extinction event has been recognized by previous studies, have the most support from the data. This suggests that the last varanopids were among the many victims of the Capitanian crisis. Our analyses also support the existence of a previously unrecognized moderate extinction event in the Asselian.